2017
DOI: 10.1038/ncomms14783
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and universal scaling law in geometrically-controlled sessile drop evaporation

Abstract: The evaporation of a liquid drop on a solid substrate is a remarkably common phenomenon. Yet, the complexity of the underlying mechanisms has constrained previous studies to spherically symmetric configurations. Here we investigate well-defined, non-spherical evaporating drops of pure liquids and binary mixtures. We deduce a universal scaling law for the evaporation rate valid for any shape and demonstrate that more curved regions lead to preferential localized depositions in particle-laden drops. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
145
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 27 publications
14
145
1
Order By: Relevance
“…This is surprising, given that previous studies observed an increase in evaporation flux with decreasing contact angles. 4,5 We attribute this to the non-homogeneous concentration gradient in the gas phase, which is the rate-limiting factor.…”
Section: Contact Angle -Heat Flux Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising, given that previous studies observed an increase in evaporation flux with decreasing contact angles. 4,5 We attribute this to the non-homogeneous concentration gradient in the gas phase, which is the rate-limiting factor.…”
Section: Contact Angle -Heat Flux Dependencementioning
confidence: 99%
“…The evaporation of droplets has shown great potential in a myriad of industrial applications, including spray coating, 1,2 spray cooling, 3,4 inkjet printing, 5,6 bio-sensing 7 and thermal management of electronic devices. [8][9][10] Droplet evaporation is affected by many parameters, such as substrate thermal properties, [11][12][13] roughness, 14,15 and wettability.…”
Section:  Introductionmentioning
confidence: 99%
“…Examples (based on numerical solutions) of both limits are shown in Figure 1. Panel (a) corresponds to a case where the regular perturbation theory holds and the resulting reduced first-order model (7) are valid. Hence, for an appropriate (small) value of , there is very close agreement between the full third-order problem and the first-order model solution (the first-order model corresponds to → 0).…”
Section: Problem Statement and Methodologymentioning
confidence: 99%
“…We determine parameter regimes wherein the reduced-order (7) is valid. The approach is twofold: we use numerical solutions to map out a parameter space where the reduced-order model is valid.…”
Section: The Reduced-order Modelmentioning
confidence: 99%
“…We can see that the velocity of the experimental point is always higher than the one predicted. This underestimation can be due to a considerable enhancement of the dissolution rate that can be expected due to the curved geometry during the zipping-depinning process [52], which has been ignored in our calculations. Additionally, it can be influenced by the underestimation of the volume brought about by our simple geometrical model.…”
Section: Theoretical Analysis Of Zipping-depinning Modementioning
confidence: 99%